Paranormal belief, conspiracy endorsement, and positive wellbeing: a network analysis - Dagnall, Neil; Drinkwater, Kenneth Graham; Denovan, Andrew; Gascón, Alex Escolá (Frontiers in Psychology, 2025)
Using network analysis (NA), this study examined interrelationships between advocacy of scientifically unsubstantiated beliefs (i.e., Paranormal and Conspiracy Endorsement) and positive wellbeing outcomes (i.e., Coping, Meaning in Life, Self-Esteem, and Satisfaction with Life). A total of 1,667 participants completed study measures. Analysis revealed that Paranormal Belief (PB) and Self-Esteem were central variables. Although not directly connected, common relationships existed with Search for Meaning in Life and Avoidant Coping. PB was most strongly linked (positively) with Conspiracy Endorsement, the Cognitive-Perceptual dimension of schizotypy, Search, and Avoidant Coping. Connections indicated that PB potentially mediated relationships between Schizotypy, Search, and Avoidant Coping. Self-Esteem was most strongly linked positively with the Presence of Meaning in Life, Active Coping, and Satisfaction with Life, and negatively with Avoidant Coping and Search. Network examination also revealed that Self-Esteem bridged relationships between Coping (Active and Avoidant), Meaning in Life (Search and Presence), and Satisfaction with Life. While the correlation between PB and Self-Esteem was small, the significance of these nodes suggested that their indirect interaction (through Search and Avoidant Coping) influenced factors related to positive wellbeing. This implied that the connection between PB and enhanced Self-Esteem positively impacted wellbeing. Conversely, PB associated with low Self-Esteem reflected poorer psychological health. Therefore, subsequent research should test this notion using specific belief facets.